Characteristics of Thyroid Carcinoma Patients at Dr. H. Abdul Moeloek Hospital for the Period of January 2023 – August 2024 - Qurani, Istiqomatul; Septiani, Linda; Kurniati, Intanri; Windarti, Indri (CV. Jasa Sukses Abadi, 2024)
Thyroid carcinoma is the most common cancer found in the endocrine system that arises from thyroid parenchymal cells. Its prevalence has increased over the past few decades with a mortality rate of 0.5% per 100,000 cases. The incidence of thyroid carcinoma in 2020 ranks 7th in the world as the 9th most frequent incidence occurs from all types of cancer. Objective: This study aims to determine the characteristics of thyroid carcinoma patients at Dr. H. Abdul Moeloek Regional General Hospital for the period of January 2023 – August 2024. Method: This study used a descriptive observational design and Total Sampling technique with a data source in the form of secondary data on medical records from 82 thyroid carcinoma patients at the Dr. H. Abdul Moeloek Regional General Hospital for the period January 2023 to August 2024. Results: In this study, thyroid carcinoma patients were mostly female, with an age group in the range of 41-60 years. The most common type of thyroid carcinoma is papillary carcinoma and the least common type is anaplastic carcinoma. Conclusion: In this study, the characteristics of thyroid carcinoma patients were obtained based on gender, age group, and type of histopathological diagnosis.